Development and Application of a Paediatric OPM-MEG System - Rhodes, Natalie (2024)
The first few years of life see rapid changes in brain function, as we grow and learn, yet the developing brain remains poorly understood. This is in part due to instrumentational constraints. Magnetoencephalography (MEG) is a non-invasive neuroimaging technique that assesses human brain function through the detection of magnetic fields generated by neural currents. As a direct measure of electrophysiology, MEG can detect changes in brain activity with a high temporal resolution. Further, by measuring across the whole head, MEG is able to probe the dynamics of brain networks as they evolve in support of cognition. MEG is therefore, in principle, the ideal tool to understand how the brain changes in the first years of life. However, conventional MEG systems are based on sensors that must be cryogenically cooled to reach the sensitivities required to detect the neuromagnetic field. As such, sensors are held in one-size-fits-all systems that require participants to remain still during data acquisition, which is not ideal for scanning young participants. MEG systems are also built for adults and therefore lack sensitivity for scanning infants and children. Recently, optically pumped magnetometers (OPMs) have emerged as a potential replacement for cryogenic sensors in MEG. OPMs are lightweight, flexible and operate without the requirement for cryogenic cooling. As such, OPMs can be placed close to the scalp surface, enabling the development of wearable MEG systems that can conform to different head sizes and allow naturalistic movement.